The impact of micronutrients on athletes’ vision: a retrospective analysis of revalent articles - I. B. Medvedev; S. A. Alieva; M. V. Gusakov; N. I. Medvedeva; N. N. Dergacheva (Спортивная медицина: наука и практика)
The eyes, like other human organs, are deficient in nutrients during over-training, which can affect visual acuity and, accordingly, the quality of training.This article defines the importance of the organ of vision for sports results. It also provides an overview of the latest scientific research on the impact of biologically significant micronutrients on the functions of the visual analyzer with examples of products that help improve visual functions.